Methylene Blue as an Adjuvant Analgesic Postoperative Anal Fistula: A Randomized Clinical Trial - Jeo, Wifanto S.; Irsal, Muhammad FA; Tamba, Riana P; Moenadjat, Yefta; Friska, Dewi (The New Ropanasuri Journal of Surgery, 2024)
Introduction. Anal fistula is a pathological condition that connects the anorectal mucosa to the perianal skin, requiring various types of surgical procedures. However, surgery often causes postoperative pain. The use of methylene blue is being studied as a potential analgetic adjuvant in anal fistula surgery. Previous studies have shown that methylene blue can effectively reduce postoperative pain in various types of anorectal surgery. This study aims to determine methylene blue's clinical efficacy as an analgetic adjuvant. Methods. A double-blind, randomized controlled trial was conducted. Subjects consisting of subjects with simple anal fistula to undergo fistulectomy were randomly allocated into two groups. The first group received adjuvant analgesics in the form of methylene blue and NSAIDs, while the second group only received NSAIDs. Methylene blue 4 mL 1% was administered subcutaneously to the edge of the wound, sprayed on the surgery site, and intravenously administered ketorolac 3 x 30 mg. Randomization was done using the double-blind method. Pain levels were evaluated on the first, second, third, and seventh postoperative days using a visual analog scale (VAS). Results. Thirty-four subjects were enrolled (17 subjects in each group). Significant differences in pain levels (VAS values) were recorded between the group receiving the combination of methylene blue and NSAIDs compared to the group receiving only NSAIDs on days 1 to 3 after surgery (p <0.05). This difference was no longer significant between the two groups on the seventh postoperative day (p >0.05). Conclusion. The use of methylene blue in subjects undergoing anal fistula surgery as an adjuvant analgesic along with NSAIDs may reduce the intensity of pain better than NSAIDs alone.